A simulation of lung ablation using microwave thermal energy - Arthorn Sanpamch (2018)
© 2015 IEEE. Since a long time ago, one of a dangerous cancer that threatening human life is pulmonary cancer. Although, an open thoracic surgery is generally realized as a conventional gold standard for this malignant, but a new therapeutic method still be proposed as an alternative choice to deal with this hazard. In this paper, we present a FEM of microwave thermal treatment to ablate cancerous region in a simple lung model. Microwave energy was trialed at 2.45GHz, 10 Watts for 10 seconds by an opened-tip coaxial antenna. By concerning with an effect of airflow ventilation, a small bronchus also placed nearby the applicator position then a thermal distribution and coagulation pattern were studied. Although, our simple model in this simulation differ from a porous lung tissue, however at 60 C destructive temperature our investigation results in term of thermal distribution and destructive zone guide us some useful predictable information for a real ex vivo experiment in the near future work.